Saturn a terabit packet switch using dual round robin. - Chao, J. (IEEE Communications magazine)
Large input-output buffering with a moderate speedup has been widely considered as the most feasible solution for large-capacity switches. We propose a new terabit per second packet switch and call it the Saturn switch. It uses a simple dual round-robin arbitration scheme to schedule packets, and achieves high throughput and low statistical delay bound. It employs a bit-sliced crossbar fabric to switch packets at 10 Gb/s at inputs and outputs, and adopts a novel token-tunneling technique to arbitrate contending packets at high speed (e.g., within 10 ns), thus achieving a switch capacity of more than 1 Tb/s with existing electronic technology.